Dampak Pandemi Covid 19 Terhadap Nilai Tukar Petani Sub Sektor Tanaman Pangan di Provinsi Jambi - Mulyani Mulyani; Nida Kemala (Universitas Batanghari Jambi, 2022)
The aim of this research is to analize impact of pandemic covid 19 to food crop sub-sector at Jambi Province. This research was using descriptive metodology. Using time series data from 2019 until 2020. The selection of locations in this study is purpossive with the consideration that Jambi Province has great potential in producing food crops., the results showed that pandemic Covid-19 did not have a direct impact on the exchange rate of farmers of the food crop sub-sector in Jambi Province but had an impact on the development of the Price Index Received by Farmers (IT) and the Farmers' Paid Price Index (IB) of the Jambi Province Food Crop Sub-Sector.